A mitochondrial targeting tetrapeptide Bendavia protects lateral line hair cells from gentamicin exposure. Issue 3 (3rd November 2017) - Kuang, Xiao; Sun, Yanhui; Wang, Zhenjie; Zhou, Shuang; Liu, Hongzhuo
Abstract: The hearing loss induced by aminoglycosides is caused by the permanent loss of mechanosensory hair cells of the inner ear. The aim of the present study is therefore to evaluate the protective effect of Bendavia, a novel antioxidant, on gentamicin‐induced hair cell damage in zebrafish lateral lines. The results demonstrated the pretreatment of Bendavia exhibited dose‐dependent protection against gentamicin in both acute and chronic exposure. We found that Bendavia at 150 μm conferred optimal protection from either acute or chronic exposure with ototoxin. Bendavia reduced uptake of fluorescent‐tagged gentamicin via mechanoelectrical transduction channels, suggesting its protective effects may be partially due to decreasing ototoxic molecule uptake. The intracellular death pathways inhibition triggered by gentamicin might be also included as no blockage of gentamicin was observed. Our data suggest that Bendavia represents a novel otoprotective drug that might provide a therapeutic alternative for patients receiving aminoglycoside treatment. Abstract : The hearing loss induced by aminoglycosides is caused by the permanent loss of mechanosensory hair cells of the inner ear. The aim of the present study is therefore to evaluate the protective effect of Bendavia, a novel antioxidant, on gentamicin‐induced hair cell damage in zebrafish lateral lines. The results demonstrated the pretreatment of Bendavia exhibited dose‐dependent protection against gentamicin in both acute and chronic exposure.